Impact of COVID-19 on Livelihood Activities of the People in District Dir Lower, Khyber Pakhtunkhwa: https://doi.org/10.5281/zenodo.16794568 - Ishaq Ahmad; Sohail Ahmad, (Dialogue Social Science Review (DSSR), 2025)
This study examines the impact of COVID-19 on the livelihood activities of people in District Dir Lower. Despite the global attention given to the pandemic's economic consequences, previous research has largely overlooked its specific impact on people's livelihood activities, and no quantitative study has been conducted in this regard in District Dir Lower. To address this gap, the present study employed a multistage purposive sampling technique for selecting respondents. Primary data were gathered using a structured questionnaire and an interview schedule. A binary logistic regression model was applied to assess the impact of COVID-19 on people's livelihood activities. The results indicate that COVID-19 has a significant impact on people's livelihood activities in District Dir Lower. The study recommends that governments and employers should offer paid sick leave and job retention programs to support employees in future pandemics. The government and private sectors should provide unconditional cash assistance to families severely impacted by the pandemic. This study provides a unique perspective on the impact of COVID-19 on the livelihood activities of people in District Dir Lower, providing valuable findings that have not explored before.